Optimalisasi Pelatihan Penggunaan Media Pembelajaran Kurikulum Merdeka Menggunakan Artificial Intelegence bagi MGMP IPA Bulukumba - Sitti Rahma Yunus; Arie Arma Arsyad; Muh. Tawil; Hasanuddin Hasanuddin (Universitas Negeri Malang, 2024)
This community service activity aims to improve the competence of Bulukumba Science MGMP participants in developing Artificial Intelligence (AI)-based learning media, in line with the Merdeka curriculum which focuses on personalized and independent learning. The scope of activities includes basic understanding of AI concepts, introduction to educational AI platforms (such as ChatGPT and Gemini), exploration of AI features for learning, and development and testing of AI-based interactive teaching media. The methods used include interactive lectures, platform demonstrations, exploratory practices, collaborative workshops, and discussions and evaluations. The initial stage of the activity began by providing an understanding of the history and concepts of AI to the exploration of the platform. Then, participants were invited to work in groups to develop and test learning media in accordance with the curriculum. The results showed an increase in teachers' understanding and skills in using AI for learning, with an average increase in competence of 51%. Evaluative discussions also identified potential improvements, particularly in the preparation of adaptive questions and visualization of science concepts. The conclusion of this activity is that this training is effective in equipping teachers with practical skills in using AI to produce engaging and personalized learning media, which can be implemented in the classroom to support students' individual needs.